Modulation of Second Messenger Signaling in the Brain Through PDE4 and PDE5 Inhibition: Therapeutic Implications for Neurological Disorders - Min Kyu Park; Hyun Wook Yang; Seo Young Woo; Dong Yeon Kim; Dae-Soon Son; Bo Young Choi; Sang Won Suh (Cells)
Phosphodiesterase (PDE) enzymes regulate intracellular signaling pathways crucial for brain development and the pathophysiology of neurological disorders. Among the 11 PDE subtypes, PDE4 and PDE5 are particularly significant due to their regulation of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) signaling, respectively, which are vital for learning, memory, and neuroprotection. This review synthesizes current evidence on the roles of PDE4 and PDE5 in neurological health and disease, focusing on their regulation of second messenger pathways and their implications for brain function. Elevated PDE4 activity impairs synaptic plasticity by reducing cAMP levels and protein kinase A (PKA) activity, contributing to cognitive decline, acute brain injuries, and neuropsychiatric conditions such as bipolar disorder and schizophrenia. Similarly, PDE5 dysregulation disrupts nitric oxide (NO) signaling and protein kinase G (PKG) pathways, which are involved in cerebrovascular homeostasis, recovery after ischemic events, and neurodegenerative processes in Alzheimer’s, Parkinson’s, and Huntington’s diseases. PDE4 and PDE5 are promising therapeutic targets for neurological disorders. Pharmacological modulation of these enzymes offers potential to enhance cognitive function and mitigate pathological mechanisms underlying brain injuries, neurodegenerative diseases, and psychiatric disorders. Further research into the regulation of PDE4 and PDE5 will advance therapeutic strategies for these conditions.